KEPEMILIKAN INSTITUSIONAL MEMODERASI PENGARUH MANAJEMEN LABA MENJELANG INITIAL PUBLIC OFFERING PADA RETURN SAHAM - Trisna Yuliawan, Komang; Pradnyantha Wirasedana, I Wayan (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
The aims of this study to determine the effect of earnings management before IPO on stock returns when considering institutional ownership as moderating variable. Information asymmetry between managers and investors demand investors more carefull on analyzing received information. Institutional ownership will give negative reacted to not valid and can’t trusted company’s information. Samples are company who do IPO and registered on Indonesian Stock Exchange year 2010-2014 as much 64 company after used purposive sampling. Data analysis technique used is interaction test or moderated regression analysis. Modified Jones model used to detect earning management. Cummulative abnormal return used as proxy of stock returns. The result shows the company do earning management one year and two year before IPO give negative effect on stock returns. These result consistent with previous study by Joni and jogiyanto (2009). This study also proved institutional ownership can weaken negative effect of earning management on stock returns
Keywords: IPO, earning management, stock returns, institutional ownership